The Republican legacy of Italy's Fascist ossuaries of the First World War. Issue 2 (15th March 2019) - Malone, Hannah
Abstract : The military ossuaries ( sacrari militari ) that were built to house the remains of fallen soldiers of the First World War offer a striking example of how Italy has dealt with the legacy of Fascism. Located along former frontlines in north-eastern Italy, the ossuaries occupy an ambiguous position in Italian heritage as both national monuments and the remnants of a difficult past. Whereas originally they functioned as instruments of Fascist propaganda, they have been reinvented as monuments of Republican Italy. Thus, while challenging the notion of Fascist remains as 'difficult heritage', this article suggests that the ossuaries might be seen as palimpsests that have been overlaid with different and ever-changing memories. To this end, the article traces the afterlives of ossuaries from 1945 to the present in search of evidence of evolving attitudes towards the Fascist period. It also examines a recent resurgence of public interest in the ossuaries in conjunction with the centenary of the First World War. Italian summary: Gli ossari (o sacrari) militari che furono costruiti per ospitare i resti di soldati caduti nella Prima Guerra Mondiale offrono un esempio rilevante di come l'Italia abbia affrontato l'eredità del regime fascista. Situati lungo il vecchio fronte nel nord-est del paese, gli ossari occupano una posizione ambigua nel patrimonio italiano in quanto sono al contempo monumenti nazionali e ricordi di un passato difficile. Sebbene fossero originariamente utilizzati come strumenti nella propaganda fascista, sono stati reinventati nel dopoguerra come monumenti dell'Italia repubblicana. Perciò, mettendo in dubbio la percezione dei resti dell'era fascista come un 'patrimonio difficile', quest'articolo suggerisce che gli ossari possano essere visti invece come palinsesti che sono stati soprapposti da ricordi diversi e mutevoli. A questo fine, l'articolo traccia la storia degli ossari dal 1945 al presente nel tentativo di fare luce sull'evoluzione di atteggiamenti verso il passato fascista. Inoltre, l'articolo esamina una recente ripresa nell'interesse del pubblico verso gli ossari in concomitanza con il centenario della prima guerra mondiale.